A novel rapid immunoassay of serum type IV collagen 7S for the diagnosis of fibrosis stage of nonalcoholic fatty liver diseases. Issue 3 (25th February 2021) - Shima, Toshihide; Ohtakaki, Yukie; Kikuchi, Hitoshi; Uchino, Hiroki; Isomura, Mitsuo; Aoyagi, Katsumi; Oya, Hirohisa; Katayama, Takayuki; Mitsumoto, Yasuhide; Mizuno, Masayuki; Umemura, Atsushi; Yamaguchi, Kanji; et al.
Abstract: Aim: Type IV collagen 7S (T4C7S) is a valuable biomarker for detecting liver fibrosis in patients with nonalcoholic fatty liver disease (NAFLD). The conventional T4C7S measurement via radioimmunoassay (T4C7S RIA) has shortcomings of radioisotope usage and longer assay periods. We compared T4C7S RIA with a newly developed, fast T4C7S chemiluminescent enzyme immunoassay (T4C7S CLEIA) and examined the diagnostic accuracies of and correlation between the two techniques. Methods: We evaluated 170 biopsy‐confirmed patients with NAFLD. T4C7S was measured via both T4C7S RIA and T4C7S CLEIA. The correlation between T4C7S RIA and T4C7S CLEIA was analyzed in 305 total serum samples via exploratory research and 47 validation samples. The diagnostic accuracies of T4C7S CLEIA and T4C7S RIA were compared in the sera of patients with NAFLD and test samples. Results: Sera T4C7S levels of T4C7S CLEIA and T4C7S RIA significantly correlated in patients' samples via exploratory ( r  = 0.914, P  = 0.000) and validation ( r  = 0.929, P  = 0.000) research. At a 10% coefficient, T4C7S CLEIA concentration was 0.26 ng/ml in the serum samples, indicating high accuracy at even low concentrations. T4C7S CLEIA revealed distinct changes between each stage and high sensitivity in detecting the F2 stage, indicating a higher sensitivity in detecting low fibrosis stages than T4C7S RIA in patients with NAFLD. Conclusions: The T4C7S CLEIA correlated well with the T4C7S RIA. Favorably, the T4C7S CLEIA has a higher sensitivity and rapid measurement time and requires a small sample volume; thus, it is a promising and popular biomarker for fibrosis stage diagnosis in NAFLD.